Senior Secondary School Teachers’ Awareness, Use and Constraints of Edulastic Application for Curriculum Content Delivery in Kwali, Abuja - OTEMUYIWA, Bridget Idowu; MEFUN, Fredrick Ebimobowei (Ilorin Journal of Education, 2023)
The study evaluated senior secondary school teachers’ level of awareness, use and constraints encountered in edulastic application in the delivery of curriculum contents in Kwali Area Council of Abuja. The study adopted descriptive survey research design. The population for the study comprised all the 144 teachers in the six senior secondary schools in the Area Council. The sample for the study was made up of 96 teachers conveniently selected from four senior secondary schools (2021/2022) academic session. The instrument for data collection was developed by the researchers titled: “Level of Awareness, Use and Constraints of Edulastic Application Questionnaire (LAUCEAQ)”. The instrument was pilot tested on 10 senior secondary school teachers not covered in the study. Cronbach Alpha was employed to determine its reliability coefficient that yielded r=.89. The instrument was administered on the respondents by the researchers and a 100% return rate was achieved. Data collected were analyzed using frequency counts, percentages and mean set values of 2.50 – 3.00, 1.51-2.49 and 0.50 - 1.50 representing high, moderate and low extents respectively. Findings revealed teachers’ low level of awareness and use of edulastic application. Among the constraints encountered by the senior secondary teachers include: lack of awareness, poor supply of electricity, low or weak network/bandwidth and non-integration of technology in the subject curricula.